2018
DOI: 10.1002/joc.5430
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐monthly variability of the South American summer precipitation under El Niño and La Niña backgrounds during the 1998–2012 period

Abstract: The sub‐monthly intra‐seasonal 8–24‐day period (SIS8‐24) timescale variability of the summer (1 November to 31 March) rainfall over South America (SA) under distinct inter‐annual (IA) backgrounds was analysed using the Tropical Rainfall Measure Mission (TRMM) based daily total precipitation data for the 1998–2012 period. The IA backgrounds refer to the El Niño (EN) and La Niña (LN) years. First, the summer daily precipitation anomaly fields were subject to the empirical orthogonal function (EOF) analysis. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The Niño3.4 index is highly anti‐correlated with the SOI; hence it comes as no surprise that it is positively correlated with the SPEI index, consistent with abundant literature on the ENSO hydroclimate influence in central Chile (e.g., Montecinos and Aceituno, 2003; Erfanian et al ., 2017; Amaro de Lima et al ., 2018). However, slightly higher correlations in all months were expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Niño3.4 index is highly anti‐correlated with the SOI; hence it comes as no surprise that it is positively correlated with the SPEI index, consistent with abundant literature on the ENSO hydroclimate influence in central Chile (e.g., Montecinos and Aceituno, 2003; Erfanian et al ., 2017; Amaro de Lima et al ., 2018). However, slightly higher correlations in all months were expected.…”
Section: Discussionmentioning
confidence: 99%
“…These climatic characteristics are further modulated by the orography, due to an altitudinal range of more than 3,000 m across less than 100 km from the Pacific coastline to the summits of the Andes. It has been shown that modes of interannual to multi‐decadal variability (such as the Pacific Decadal Oscillation [PDO], and ENSO) explain a large fraction of south‐central Chile rainfall (Quintana and Aceituno, 2012; Amaro de Lima et al ., 2018). These modes also affect low‐level atmospheric circulation in this area (Sarricolea et al ., 2018) and the occurrence of extreme events (Erfanian et al ., 2017).…”
Section: Study Area Data Sets and Methodological Approachmentioning
confidence: 99%